PERANG WACANA ISLAMISME DI MESIR: PERSPEKTIF LINGUISTIK - Irsyady, Kamran As'at (Analisis: Jurnal Studi Keislaman, 2013)
Egypt is the ‘Mecca’ of modern Islamic thoughts.  From Egypt, Islamic   thoughts,   both   secular   and   traditional,    have   been distributed  to all parts of the Islamic world. In his book, Jacob Hoigilt seeks to record and present the fierce discourse between Islamism vis-a-vis West-secularism from the perspective of linguistic disciplines. The authors conducts a critical analysis of the language (language/parole)  used by Islamic thinkers  in their polemic about Islamism, its meaning construction, as well as social situation underlying the polemic in Egypt. The author thoroughly scrutinizes  the texts of the islamist   thinkers, as well as clarifies the issues of symbolic power struggles, orthodoxy, and ideology that divide the intellectuals  into liberalist and Islamist poles.